Data storytelling and visualization with Tableau : a hands-on approach - Joshi, Prachi; Mahalle, Parikshit N. (Boca Raton : CRC Press, 2023)
"With the tremendous growth and availability of the data, this book covers understanding of the data, while telling a story with visualization including basic concepts about the data, the relationship, and the visualizations. All the technical details that include installation and building the different visualizations are explained in clear and systematic way. Various aspects pertaining to storytelling and visualization are explained in the book through Tableau. Features: Provides a hands-on approach in Tableau in a simplified manner with steps. Discusses the broad background of data and its fundamentals, Internet of everything to analytics. Emphasizes the use of context in delivering the stories. Presents case studies with building of a dashboard. Presents application areas and case studies with identification of the impactful visualization. This book aims at Professionals, Graduate students and senior under-graduate students in Manufacturing Engineering, Civil and Mechanical Engineering, Data Analytics, and Data Visualization"--
Data storytelling -- Data visualization -- Visualization with Tableau.
OCLC-licensed vendor bibliographic record.
Keywords: Tableau (Computer file); Information visualization -- Computer programs; COMPUTERS / Computer Graphics / General; TECHNOLOGY / Electricity; TECHNOLOGY / Imaging Systems